TUBEROUS SCLEROSIS - RARE PRESENTATION AS PNEUMOTHORAX - Khan, Nisar; Javed, Arshad; Wazir, Samad; Yousaf, Muhammad (Journal of Ayub Medical College Abbottabad, 2003)
Pulmonary disease is a rare manifestation of Tuberous Sclerosis. We report a case where the patient presented with seizures, shortness of breath, popular lesions on the face and warty growths over the skin. She was intubated and the lung expanded on the 7th day after a longstanding pneumothorax of 3 months. Key Words: Pneumothorax, Tuberous Sclerosis, Seizures.